Surgical Antibiotic Prophylaxis is not Associated with Risk for Post-Operative Antibiotic-Resistant Infections. (4th October 2017) - Cohen, Margot; Salmasian, Hojjat; Li, Jianhua; Liu, Jianfang; Zachariah, Philip; Wright, Jason; Freedberg, Daniel
Abstract: Background: Antibiotic-resistant infections are increasingly common and have high rates of morbidity and mortality. Exposure to antibiotics is the crucial risk factor for antibiotic-resistant infections. If surgical antibiotic prophylaxis (SAP) increases risk for antibiotic-resistant infections, prophylaxis may cause net harm even if it decreases overall infection rates. Methods: This retrospective cohort study involved adults that underwent elective surgical procedures at a tertiary care medical center and developed infections within 90 post-operative days. Surgeries were chosen from multiple disciplines and were included if SAP was considered discretionary according to current guidelines. Post-operative antibiotic-resistant infections were defined as positive culture results from any site or fluid showing non-susceptibility in one or more antibiotic classes. SAP was defined as the use of antibiotics within any class and at any dose from 1 hour before the first incision until the end of the operation. Results: 1, 059 adults had post-operative infections. 517 (49%) were classified as having post-operative resistant infections. The use of SAP was not associated with post-operative antibiotic-resistant infections (OR 1.04, 95% CI 0.77–1.41). This result remained robust when the definition of SAP was extended to antibiotics given within 4 hours before the first incision (OR 0.97, 95% CI 0.72–1.32) and when the definition of resistant infections was narrowed to include only multi-drug-resistant infections (OR 1.32, 95% CI 0.88–1.97). There was no evidence of class-specific antibiotic resistance (e.g., the use of cephalosporins and subsequent cephalosporin resistance). Prior antibiotic-resistant infections were associated with risk for post-operative antibiotic-resistant infections (OR 2.21, 95% CI 1.54–3.17). Conclusion: The use of SAP was not associated with risk for post-operative antibiotic resistant infections in a large cohort of patients with post-operative infections. Prior antibiotic resistance was the most important risk factor for post-operative resistance. Discretionary use of SAP is likely a low-yield target for antibiotic stewardship efforts. Disclosures: All authors: No reported disclosures.